2017
DOI: 10.1186/s13643-017-0576-6
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of common metabolic risk factors (high blood pressure, high blood sugar, high body mass index and high waist-hip ratio) of major non-communicable diseases in South Asia region: a systematic review protocol

Abstract: BackgroundPrevalence of non-communicable diseases has been increasing at a greater pace in developing countries and, in particular, the South Asia region. Various behavioral, social and environmental factors present in this region perpetuate common metabolic risk factors of non-communicable diseases. This study will identify social determinants of common metabolic risk factors of major non-communicable diseases in the context of the South Asian region and map their causal pathway.MethodsA systematic review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…We used a causal loop diagram (CLD)—a tool based on System Dynamics -- to further expand on our analysis of CMD epidemiology and migration policies in South Asia [12]. The authors (SRM, SRS) have used CLD in NCD context before [13]. The CLD shows the linkages between social determinants of CMD risk factors, and how these determinants reinforce or balance each other under a prevailing policy context.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a causal loop diagram (CLD)—a tool based on System Dynamics -- to further expand on our analysis of CMD epidemiology and migration policies in South Asia [12]. The authors (SRM, SRS) have used CLD in NCD context before [13]. The CLD shows the linkages between social determinants of CMD risk factors, and how these determinants reinforce or balance each other under a prevailing policy context.…”
Section: Methodsmentioning
confidence: 99%
“…‘R’ denotes a reinforcing loop and ‘B’ denotes a balancing loop. More description about them is available in reference [12] and [13]. Abbreviations: CMD: cardio metabolic disease;’ SE: socio-economic…”
Section: Way Forwardsmentioning
confidence: 99%
“…17,18 Studies have shown that when the mesangial cells are stimulated by hyperglycemia, TGF-b1 synthesis is increased and extracellular matrix is deposited by induction. 19 Smad protein is the only substrate of TGF-b1 signaling pathway; when expression of TGF-b1 is upregulated, expression of Smad protein is increased correspondingly, which may lead to transduction of the TGF-b1 signal from the receptor to the nucleus, accelerating the process of tissue fibrosis. 20 Studies have shown that expression of Smad3 in fibrotic kidney tissue is significantly upregulated 21 and that when the Smad3 gene is knocked out from renal tubular epithelial cells, Ang II-induced matrix is significantly reduced and renal fibrosis process may be stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Thematic analysis and brainstorming with authors’ own reflexivity helped in constructing these causal loop diagrams (CLDs). More description about causal loop diagrams and its application in decision making is available in the reference [ 47 – 49 ]. For further information in CLDs, please follow the online resource from the John Hopkins University ( https://www.coursera.org/learn/systems-thinking ) …”
Section: Methodsmentioning
confidence: 99%